YAP repression of the WNT3 gene controls hESC differentiation along the cardiac mesoderm lineage - Estarás, Conchi (Genes Dev, 2017)
Activin/SMAD signaling in human embryonic stem cells (hESCs) ensures NANOG expression and stem cell pluripotency. In the presence of Wnt ligand, the Activin/SMAD transcription network switches to cooperate with Wnt/β-catenin and induce mesendodermal (ME) differentiation genes. We show here that the Hippo effector YAP binds to the WNT3 gene enhancer and prevents the gene from being induced by Activin in proliferating hESCs. ChIP-seq (chromatin immunoprecipitation [ChIP] combined with high-throughput sequencing) data show that YAP impairs SMAD recruitment and the accumulation of P-TEFb-associated RNA polymerase II (RNAPII) C-terminal domain (CTD)-Ser7 phosphorylation at the WNT3 gene. CRISPR/CAS9 knockout of YAP in hESCs enables Activin to induce Wnt3 expression and stabilize β-catenin, which then synergizes with Activin-induced SMADs to activate a subset of ME genes that is required to form cardiac mesoderm. Interestingly, exposure of YAP(−/−) hESCs to Activin induces cardiac mesoderm markers (BAF60c and HAND1) without activating Wnt-dependent cardiac inhibitor genes (CDX2 and MSX1). Moreover, canonical Wnt target genes are up-regulated only modestly, if at all, under these conditions. Consequently, YAP-null hESCs exposed to Activin differentiate precisely into beating cardiomyocytes without further treatment. We conclude that YAP maintains hESC pluripotency by preventing WNT3 expression in response to Activin, thereby blocking a direct route to embryonic cardiac mesoderm formation.